Presidential Decree-Law No. 230/2016 Issuing The Executive Regulations of the Electricity Law Issued as per Law No. 87/2015 = قرار وزاري رقم 230 لسنة 2016 بإصدار اللائحة التنفيذية لقانون الكهرباء الصادر بالقانون رقم 87 لسنة 2015 / Presidency. - Egypt. Presidency. (2025)
1. Definitions -- 2. The organization of the electric utility -- 3. Electricity activities -- 4.Improving the efficiency of energy use -- 5. Electric Utility Facilities -- 6. The transitional period and the competitive electricity market.